Escarcéu e escassez no teatro de Mossoró: percursos e percalços de uma dramaturgia na rua - Costa, Raimundo Nonato Santos da (2011)
This research is a result of the theatrical Street show named A Árvore dos Mamulengos, an appropriation of the drama text by Vital Santos, this presentation was done from 1989 to 2001, with the Companhia Escarcéu de Teatro, in the city of Mossoró/RN, Brazil. The intention here is to mapping the voices and memories of actors and actresses who have experienced the performance, the developments and achievements which resulted from twelve years of the season. In our study, we consider the importance of the choice for the open space such as streets and squares as the main local for representation considering it as a catalyst factor of aesthetic choice. However, we`ve consider the option for the collaborative process as the methodology staging by interpreters, as well as, the social and cultural determinants that were taking place deeming the realization of the spectacle